The secret files of Gilbert and George [2000] : documentaire - Obrist, Hans Ulrich (Paris : Bureau des Videos, 2007)
Gilbert Proesch and George Passmore met as students in 1967 and have been working together ever since. Italian and British respectively, they are known by a combination of their first names and have always put themselves at the center of their art. For the last 40 years, Gilbert & George have spanned the international art scene with as much insolence as elegance. This interview by modern art curator Hans Ulrich Obrist focuses on Gilbert & George's archiving system. In it, they discuss not only what they keep (all of their own images, plus all articles in the media about themselves), but how it is ordered (images are coded by color) and their observation on the headlines they are afforded, and what they say about the times in which they were written.
This film was made for the exhibition "VoilaÌ, le monde dans la teÌte" [This is the world in the head] at the Modern Art Museum of the City of Paris from June 15 to October 29, 2000
In English with optional subtitles in French
film
Keywords: Gilbert & George; Obrist, Hans-Ulrich